(untitled) (Research, Society and Development, 2022)
Cancer is a pathology that challenges most individuals, especially children, taking into account worldwide, because it is a disease that greatly affects the lives of this group. This study aims to understand the role of nurses in palliative care for children with cancer. The present study is an integrative review with an exploratory, descriptive and qualitative approach. The collection of information was carried out through the Virtual Health Library where the database of Latin American and Caribbean Literature on Health Sciences (LILACS) was selected and to carry out the collection of scientific articles we used the keywords: Nursing, Palliative Care and Cancer. It can be highlighted how the results of physical and psychological changes are evidenced in patients with Ca, pain, suffering, anguish and guilt are characterized as the feelings of family members and the nurse acts through the provision of palliative care and psychological assistance to both the patient regarding their family members. The professional nurse is in charge of performing the necessary care for individuals who need palliative care in the hospital environment or in their homes. It is concluded that the care provided by nurses is essential for safe and effective care, since pain and suffering are common in cancer patients and their families.